2009
DOI: 10.1007/s00586-009-1104-8
|View full text |Cite
|
Sign up to set email alerts
|

Transpedicular closed wedge osteotomy in ankylosing spondylitis: results of surgical treatment and prospective outcome analysis

Abstract: Surgery in late stage ankylosing spondylitis (AS) most often tends to correct the sagittal balance with an extension osteotomy of the spine. In the literature, extension osteotomy was first described as an open wedge osteotomy but recently closed wedge osteotomy resecting the pedicles and posterior elements have become more popular. Only a limited number of cases have been reported in the literature and with limited focus on outcome of this major surgery. In this study, we reported the results of a large serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 19 publications
2
63
0
2
Order By: Relevance
“…Third, the anterior and middle column at the segment of the bony defect will be functionally unstable; an iliac graft packed between the vertebral bodies can support the anterior and middle column structurally to restore the stability, and can achieve bony surfaces contact contributing to a rapid healing. Fourth, the presence of a gap in the anterior column may place excessive loads on the posterior instrumentation and compromise stability of the construct, which increases the incidence of late complications such as loss of correction or instrumentation failure [5,15]. In this situation, an anterior strut graft can effectively reduce the stresses that act on the posterior instrumentation to prevent the above-mentioned complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the anterior and middle column at the segment of the bony defect will be functionally unstable; an iliac graft packed between the vertebral bodies can support the anterior and middle column structurally to restore the stability, and can achieve bony surfaces contact contributing to a rapid healing. Fourth, the presence of a gap in the anterior column may place excessive loads on the posterior instrumentation and compromise stability of the construct, which increases the incidence of late complications such as loss of correction or instrumentation failure [5,15]. In this situation, an anterior strut graft can effectively reduce the stresses that act on the posterior instrumentation to prevent the above-mentioned complications.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic inflammation causes progressive ossification of the spinal ligaments and facet joints, which eventually results in a fixed and rigid spine [7,8,15]. In addition, AS is also associated with vertebral osteoporosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of correction was not great enough, especially for severe thoracic deformities. Moreover, a rather high complication rate was also shown [18][19][20][21][22][23]. Bridwell et al found an 11.1% rate of neurological deficits and a 2.8% rate of permanent deficits [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical technique must be adapted to the amount of correction: PSO average correction is 30°, Smith-Petersen/Chevron: 8-10°per level [6]. Strong sacral or sacroiliac fixation is requested with good posterolateral grafting [7,8]. Cage at the level L5/S1 and L4/L5 is often requested if the disc is high to avoid loss of correction.…”
Section: Discussionmentioning
confidence: 99%